Fonologi Bahasa Minangkabau Isolek Sikucur - Nastiti Kharisma; Nadra Nadra; Reniwati Reniwati (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2021)
Minangkabau language is one of the regional languages ​​in Indonesia. The purpose of this study was to determine the sounds, phonemes and their distributions in Minangkabau language of Sikucur isolect. The observation and interview methods were used to obtain data. During the interview, the results of the interview were recorded and phonetic transcription was made based on IPA chart. Furthermore, the method used to analyze the data was a phonetic articulator matching method. The data that had been collected was classified according to sound pairs that were phonetically similar. The results showed that there were 30 phonemes found. There were five vowels: /i/, /e/. /a/, /u/, and /o/. Each vowel had an allophone, namely [i~ɪ], [e~ɛ], [a~ʌ], [u~ʊ], dan [o~ɔ]. There were seven diphthongs: /aw/, /ay/, /uy/, /ua/ with allophones [ua~ue], /ia/ with allophones [ia~ie], /oy/, and /ea/. Finally, there were eighteen consonants: /p/, /b/, /m/, /t/, /d/, /n/, /l/, /ʀ/, /s/, /c/, /j/ , /ɲ/, /k/, /g/, /ŋ/, /h/, /w/, and /y/. The sound [ʔ] was the realization of /k/ when it was at the end of the closing syllable. Furthermore, [ʀ] and [r] were free variations and did not differentiate in meaning.